Photostable AIE probes for wash-free, ultrafast, and high-quality plasma membrane staining. Issue 21 (28th April 2021) - Sayed, Sayed Mir; Jia, Hao-Ran; Jiang, Yao-Wen; Zhu, Ya-Xuan; Ma, Liang; Yin, Feifei; Hussain, Imtiaz; Khan, Arshad; Ma, Qian; Wu, Fu-Gen; Lu, Xiaolin
Abstract : We develop an organic fluorescent probe based on aggregation-induced emission for rapid, wash-free, and stable plasma membrane imaging. Abstract : Plasma membrane (PM), a fundamental building component of a cell, is responsible for a variety of cell functions and biological processes. However, it is still challenging to acquire its morphology and morphological variation information via an effective approach. Herein, we report a PM imaging study regarding an aggregation-induced emission luminogen (AIEgen) called tetraphenylethylene–naphthalimide + (TPE–NIM + ), which is derived from our previously reported tetraphenylethylene–naphthalimide (TPE–NIM). The designed AIEgen (TPE–NIM + ) shows significant characteristics of ultrafast staining, high photostability, wash-free property, and long retention time at the PM, which can structurally be correlated with its positively charged quaternary amine and hydrophobic moiety. TPE–NIM + is further applied for staining of different cell lines, proving its universal PM imaging capability. Most importantly, we demonstrate that TPE–NIM + can clearly delineate the contours of densely packed living cells with high cytocompatibility. Therefore, TPE–NIM + as a PM imaging reagent superior to currently available commercial PM dyes shall find a number of applications in the biological/biomedical fields and even beyond.